2015
DOI: 10.1021/acs.jpcb.5b08432
|View full text |Cite
|
Sign up to set email alerts
|

Water-like Anomalies and Phase Behavior of a Pair Potential that Stabilizes Diamond

Abstract: Water, silicon, silica, and other liquids that favor tetrahedral order display thermodynamic, dynamic, and structural anomalies in the pressure range in which they form tetrahedrally coordinated crystals. The tetrahedral order in these liquids is induced by anisotropic hydrogen bonding or covalent interactions, or, in ionic melts, by an appropriate size ratio of the ions. Simple isotropic two-length scale models have been extensively used to understand the origin of anomalies in complex liquids. However, singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 106 publications
2
6
0
Order By: Relevance
“…It has been previously shown that the sign of the slope of the crystallization line T h (p) follows that of the melting line T m (p) for the mW and mTIP4P/2005 REM monatomic SW water models, 56 as well as the all-atom TIP4P/2005, 100 TIP4P, 51 and TIP4P/Ice, 101 and other liquids with water-like anomalies. 102 The same is observed for ML-BOP, for which dT h /dp = 0 at p ≈ −150 MPa (Figure 4). The closeness in reentrant pressures for T h (p) and T m (p) seems to be a common characteristic of all water-like liquids.…”
Section: Region Of Metastability Of Liquidsupporting
confidence: 74%
“…It has been previously shown that the sign of the slope of the crystallization line T h (p) follows that of the melting line T m (p) for the mW and mTIP4P/2005 REM monatomic SW water models, 56 as well as the all-atom TIP4P/2005, 100 TIP4P, 51 and TIP4P/Ice, 101 and other liquids with water-like anomalies. 102 The same is observed for ML-BOP, for which dT h /dp = 0 at p ≈ −150 MPa (Figure 4). The closeness in reentrant pressures for T h (p) and T m (p) seems to be a common characteristic of all water-like liquids.…”
Section: Region Of Metastability Of Liquidsupporting
confidence: 74%
“…hR 3-α is one of the lowest-coordinated structures found in this study and is a 2-coordinated columnar structure where particles are hexagonally arranged and have nearest neighbors only within these columns, arranged along the c -axis. This structure seems to correspond to another structure found in a previous computational study investigating the pressure-induced structures of a diamond-type phase . Here, we find that the structure can be simulated without applying an elevated pressure.…”
Section: Resultssupporting
confidence: 84%
“…The recent interest in the study of complex systems has led to an increased focus on anomalous diffusion [4-7, 36, 42, 45], which has been described in biological systems [42][43][44], protostellar birth [47], complex fluids [48][49][50][51][52][53], electronic transportation [54][55][56][57][58][59], porous media and infiltration [60][61][62], drug delivery [63][64][65][66], fractal structures and networks [67][68][69][70][71], and in water's anomalous behavior [72][73][74], phase transitions in synchronizing oscillators [39,40,[75][76][77], to name a few.…”
Section: Breakdown Of the Normal Diffusive Regimementioning
confidence: 99%